Geoprocessamento e contaminação de solo por ovos de Toxocara spp. em áreas de lazer e recreação - Marchioro, Ariella Andrade (2012)
Geographic information system (GIS) or Health geography is a geographical identification of the spatial variation of contagion disease and zoon sis risk in certain conditions. This study aimed to evaluate the use of GIS as a tool to identified spatial variation of Toxocara spp. contamination in recreational urban areas at Northwest Paraná, Brazil, also to compare sand and grass structures content. Were investigated 98% of Parana recreational urban areas such as, schools, public parks and squares filled with sand and/or lawn. Samples were analyzed using zinc sulphate solution centrifuge-flotation, density 1.420, and water sedimentation. Maps were developed by ESRI Arc GIS 9.2. Results: Total 77/98 (78,6%) of public spaces shown Toxocara spp. eggs presence. No significant difference were observed (p=0,9999) between eggs prevalence in sand 44/56 (78,6%), and lawn 33/42 (78,6%), at school (p=0,6898) and squares(p=0,0616). Egg contamination prevailed in periphery areas in the sand 20/27 (74%) and lawn18/21 (86%). However, no significant difference were observed between sand and lawn contamination from schools and parks to central and peripheral areas. Although schools 62/66(93,9%) presented a higher number of enclosed spaces, did not provide a lower frequency of pollution (p=0.3327). GIS observed a scattered pattern of zoon sis among schools and public squares sand and lawns, with predominance of contamination in the peripheral areas with presence of dogs/cats.